Evaluation of Sustainable Performance of Economic Unit (Entrepreneurship Journal for Finance and Business, 2022)
The problem of research has been reflected in the absence of interest of economic units in information on environmental and social costs needed to measure maintainable performance and in the fact that those economic units simply account for the elements of costs used in the production of products without considering the environmental and social costs in determining the cost of the product for the purpose of addressing this problem, this research is aimed at studying and indicating the impact of environmental and social cost accounting on the sustainable functioning of the economic unit. The nature of the accounting system applied in the economic unit in question is identified as the Ground of Architecture Cement Manufacturing Company, for the purpose of achieving the objectives of research and hypothesis testing, the Land of Architecture Cement Manufacturing Company, located in Misan governorate, has been selected environmental and social costs have not been measured, assessed and revealed as costs distinctly from other costs in the balance sheets, as it has been shown through the applied study that the environmental and social costs of the economic unit in question are hidden among other costs, leading to unsuitable management decisions, and thus negatively affecting the validity of the financial lists and reports of the economic unit. Through the statistical investigation of the questionnaire form, it was found that environmental and social cost accounting had a positive impact on raising the level of production, sales and occupational safety of workers, as well as on the reduction or decrease of environmental risks in the economic unit, as well as its positive impact on the valuation of the maintainable performance of the economic unit in question.